2015
DOI: 10.1016/j.optmat.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental analysis of the angular distribution of the emitted light from the edge of luminescent solar concentrators

Abstract: Luminescent solar concentrators (LSC) have the potential to provide cheap solar electricity by significantly reducing the solar cell area. However, these devices are still at the research level and several aspects of their behaviour need investigation in order to improve efficiencies. Understanding how light is absorbed/emitted and concentrated to the edge of LSCs is required to design a high efficiency device as well as identifying and overcoming the various losses present. One strategy for investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The modelization of LSCs has been developed in numerous publications. [33][34][35][36][37][38][39][40][41][42][43][44][45][46] Some of them are essentially focused on the thermodynamics aspects of light conversion, [33][34][35][36][37][38][39][40] while other loss factors and in particular SA or recent technical developments such as photonic band filters or chromophore orientation have been also considered with the aid of ray-tracing programs and Monte-Carlo methods. [41,42] In many cases, modelization focuses on some particular factors while some others are neglected, for example, matrix absorption, or assumed to be quantitative, for instance TIR or φ PL .…”
Section: Coupling With Pv Cellsmentioning
confidence: 99%
“…The modelization of LSCs has been developed in numerous publications. [33][34][35][36][37][38][39][40][41][42][43][44][45][46] Some of them are essentially focused on the thermodynamics aspects of light conversion, [33][34][35][36][37][38][39][40] while other loss factors and in particular SA or recent technical developments such as photonic band filters or chromophore orientation have been also considered with the aid of ray-tracing programs and Monte-Carlo methods. [41,42] In many cases, modelization focuses on some particular factors while some others are neglected, for example, matrix absorption, or assumed to be quantitative, for instance TIR or φ PL .…”
Section: Coupling With Pv Cellsmentioning
confidence: 99%
“…An increase in the extracted power of up to 50% was observed, corresponding to a concentration factor of 8. The intensity indicatrix was measured in one angular dimension with a simplified version of the experiment described by Parel et al [23] that is shown in Fig. 3a.…”
Section: Experime Unpolishedmentioning
confidence: 99%
“…The solar reflector aims to receive maximum solar radiation that can maximize the output power. An FTCC method is proposed in (Parel et al, 2015) that considers the angular distribution of light to enhance PV system efficiency. An FTCC technology is developed in (Wu et al, 2016) that includes 3-D tracking techniques.…”
Section: Floating Tracking Cooling Concentrator Systemmentioning
confidence: 99%